Sport as a Means of Promoting Universal Humanistic Values - Bilous, Anton (Journal of Education, Health and Sport, 2021)
Aim. Conceptualization of the axiological potential of sport as an important social phenomenon that covers all levels of modern society. Material and methods. The theoretical and methodological basis of our study is: 1) works of Ukrainian and foreign scientists in the process of learning the essence of sport, its place in the socio-cultural space; 2) the results of modern cultural studies; 3) speculations of representatives of axiological knowledge. The specifics of the theoretical study also determined the need to involve a number of scientific approaches to the analysis of the phenomenon of sport: 1) systemic; 2) personality-oriented; 3) axiological; 4) culturological. Results. The analysis of the special literature on the chosen topic provided the basis for: 1) determining the formation of humanistic values ​​of the task relevant to the society; 2) conceptualization of the basic conditions for the promotion of the following values ​​(gaining value experience by engaging in axiological knowledge and examples of success of life strategies based on humanistic values; involvement in the value reality, which formulates clear requirements for the individual in combination with creating conditions to meet its needs ); 3) appeal to sport as a specific phenomenon of cultural life and a source of a significant number of examples of success of life strategies based on humanistic values; 4) highlighting the potential of sport in terms of promoting universal humanistic values. Conclusions. Special studies prove that the topic of humanistic values ​​does not lose relevance. Accordingly, the task is to ensure their promotion in society. There are reasonable grounds to claim that one of the means of solving this problem is modern sport. It is the social phenomenon that has the potential to provide the basic conditions for the promotion of humanistic values: 1) considerable space for gaining valuable experience; 2) effective involvement in the value reality.